MiR-7/EGFR/MEGF9 axis regulates cartilage degradation in osteoarthritis via PI3K/AKT/mTOR signaling pathway. Issue 1 (1st January 2021) - Jiang, Lifeng; Zhou, Xindie; Xu, Kai; Hu, Pengfei; Bao, Jiapeng; Li, Jin; Zhu, Junfeng; Wu, Lidong
ABSTRACT: Osteoarthritis (OA) is a common degenerative disease in middle-aged and elderly people. Our previous study has proved that microRNA-7 (miR-7) exacerbated the OA process. This study was aimed to explore the downstream genes and mechanism regulated by miR-7 to affect OA. Multiple EGF-like-domains 9 (MEGF9) was the predicted target of miR-7 by databases. Luciferase report experiment results confirmed that MEGF9 could bind to miR-7. Among the 10 collected pairs of OA and healthy samples, the expression levels of miR-7 and MEGF9 were both up-regulated when compared with healthy subjects by qRT-PCR and immunohistochemistry (IHC). The increased MEGF9 levels were due to the interaction with epidermal growth factor receptor (EGFR) by co-immunoprecipitation. Evaluations found that upregulation of miR-7 or MEGF9 can increase the expression of EGFR, matrix metalloproteinase-13 (MMP-13) and a disintegrin like and metallopeptidase with thrombospondin type 1 motif 5 (ADAMTS-5), so as to aggravate cartilage degradation. In addition, this effect induced by miR-7/EGFR/MEGF9 axis was by activation of PI3K/AKT signaling. The IHC and western blot assay results on OA model mice also demonstrated that miR-7/EGFR/MEGF9 axis regulated cartilage degradation in vivo. In summary, miR-7/EGFR/MEGF9 axis may perform a crucial function in the regulation of OA, providing potential for OA treatment.